2009
DOI: 10.1007/s11269-009-9498-y
|View full text |Cite
|
Sign up to set email alerts
|

Testing a Dynamic Complex Hypothesis in the Analysis of Land Use Impact on Lake Water Quality

Abstract: In this study, we proposed a dynamic complex hypothesis that the impact of land use on water quality could vary along the expansion of the buffer size, and there should be an effective buffer zone where the strongest linkage occurs between land use and water quality. The hypothesis was tested and supported by a case study carried out in four watersheds in Hanyang District, China. More specific, buffer analysis and regression model were applied for studying the impacts of land use type, area proportion of land … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 44 publications
1
31
1
Order By: Relevance
“…Others have used OLS regression to show that built-up land is positively associated with water pollution (Galbraith and Burns, 2007;Bahar et al, 2008;Hertler et al, 2009;Tran et al, 2010;Kang et al, 2010;Guo et al, 2010;Huang et al, 2014Huang et al, , 2013a. We also drew similar conclusions using Pearson correlation analysis (Table 1).…”
Section: Effect Of Built-up Land On Water Pollutionsupporting
confidence: 68%
See 1 more Smart Citation
“…Others have used OLS regression to show that built-up land is positively associated with water pollution (Galbraith and Burns, 2007;Bahar et al, 2008;Hertler et al, 2009;Tran et al, 2010;Kang et al, 2010;Guo et al, 2010;Huang et al, 2014Huang et al, , 2013a. We also drew similar conclusions using Pearson correlation analysis (Table 1).…”
Section: Effect Of Built-up Land On Water Pollutionsupporting
confidence: 68%
“…Inconsistency is well documented in terms of seasonal or inter-annual variations (Sliva and Williams, 2001;Kaushal et al, 2008;Lee et al, 2009;Huang et al, 2013a), spatial scale effects (e.g. buffer versus entire watersheds) (Sliva and Williams, 2001;Uuemaa et al, 2005;Guo et al, 2010;Tran et al, 2010;Pratt and Chang, 2012) and watershed characteristics represented by various dominant land uses such as woodland, built-up, and mining (Mehaffey et al, 2005;Xiao and Ji, 2007;Bahar et al, 2008). The methods used in most of the abovementioned studies are conventional global statistical methods, such as Pearson correlation analysis (Tong and Chen, 2002;Galbraith and Burns, 2007;Bahar et al, 2008;Lee et al, 2009;Sun et al, 2011b) and multiple regression (Sliva and Williams, 2001;Fedorko et al, 2005;Huang et al, 2013a;Yang, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Other research studies have also provided evidence of a strong relationship between land use type and the water quality characteristics in a catchment area [7,10].…”
Section: Introductionmentioning
confidence: 92%
“…The positive relation of urban land with NO 2 -N, DO and NO 3 -N should also be noted. Because urban land was always considered to be an important variable that was associated with water quality variables (Reimann et al, 2009;Guo et al, 2010), urban areas tend to have low concentration of DO (Huang et al, 2013), which may result in impeded nitrification. Accordingly, our study demonstrated that urban land was negatively associated with DO.…”
Section: Agriculture Landmentioning
confidence: 99%